Polymorphic Amplified Typing Sequences and Pulsed-Field Gel Electrophoresis Yield Comparable Results in the Strain Typing of a Diverse Set of Bovine Escherichia coli O157:H7 Isolates. (23rd September 2012) - Kudva, Indira T.; Davis, Margaret A.; Griffin, Robert W.; Garren, Jeonifer; Murray, Megan; John, Manohar; Hovde, Carolyn J.; Calderwood, Stephen B.
Abstract : Polymorphic amplified typing sequences (PATS), a PCR-based Escherichia coli O157:H7 (O157) strain typing system, targets insertions-deletions and single nucleotide polymorphisms at Xba I and Avr II restriction enzyme sites, respectively, and the virulence genes ( stx1, stx2, eae, hlyA ) in the O157 genome. In this study, the ability of PATS to discriminate O157 isolates associated with cattle was evaluated. An in-depth comparison of 25 bovine O157 isolates, from different geographic locations across Northwest United States, showed that about 85% of these isolates shared the same dendogram clade by PATS and pulsed-field gel electrophoresis (PFGE), irrespective of the restriction enzyme sites targeted. The Pearson's correlation coefficient, r, calculated at about 0.4, 0.3, and 0.4 for Xba I-based, Avr II-based and combined-enzymes PATS and PFGE similarities, respectively, indicating that these profiles shared a good but not high correlation, an expected inference given that the two techniques discriminate differently. Isolates that grouped differently were better matched to their locations using PATS. Overall, PATS discriminated the bovine O157 isolates without interpretive biases or sophisticated analytical software, and effectively complemented while not duplicating PFGE. With its quick turnaround time, PATS has excellent potential as a convenient tool for early epidemiological or food safety investigations, enabling rapid notification/implementation of quarantine measures.